Early gas kick detection in vertical wells via transient multiphase flow modelling: A review - Ahmad K. Sleiti (14778229) (2020)
Gas influx from reservoir into the wellbore during drilling, tripping, or other operations, is a hazard. In the early stages, the influx may be nearly undetectable, but the kick can rapidly change from a seemingly steady condition to one of extremely high flow rate. The resulting uncontrolled release of large amounts of gas on the drilling rig can ignite and explode; causing loss of life, loss of asset, and contamination of environment. A kick perturbs the system; analysis of the resulting transient flow could lead to significant improvement in timely detection of a kick. Timely detection is essential to avoid blowouts. Early detection also allows better characterization of potential blowout, allowing improved response and mitigation efforts. Early gas-kick prediction and analysis through dynamic multiphase flow can lead to significant progress in detection and controlling of High Pressure High Temperature (HPHT) drilling of deep wells, which is vital to prevent gas blowout risk. This review paper aims to provide the current state-of-the-art on the early gas-kick simulation models based on transient multiphase flow to determine the bottom hole pressure and gas kick size and to employ appropriate mitigation plans. A comprehensive literature review on early kick detection showed that the transient one-dimensional two-phase models are prominently researched considering some aspects of heat transfer, gas solubility and homogenous flows. The reported transient two-phase (G-L) flow models are found to be limited to 1-D flow with limited range of operating conditions. Future studies towards more sophisticated 2-D and 3-D simulations of transient multiphase (G-L) flow models using computational fluid dynamics (CFD) tools are recommended. 2-D and 3-D flow simulations using advanced turbulence models can potentially enhance the accuracy in the calculations of phase velocity, temperature and pressure patterns within the annuli of wellbore and can advance the early gas-kick detection process. Other Information Published in: Journal of Natural Gas Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jngse.2020.103391